2019
DOI: 10.1007/s11145-019-09953-8
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the keystroke log: the effect of writing task on keystroke features

Abstract: Keystroke logging is used to automatically record writers' unfolding typing process and to get insight into moments when they struggle composing text. However, it is not clear which and how features from the keystroke log map to higher-level cognitive processes, such as planning and revision. This study aims to investigate the sensitivity of frequently used keystroke features across tasks with different cognitive demands. Two keystroke datasets were analyzed: one consisting of a copy task and an email writing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
12

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 54 publications
0
14
0
12
Order By: Relevance
“…In addition, the fluency effect in this research is consistent across writing genres. It echoes back to Conijn et al’s (2019) finding, that is, the features, particularly for within words, are robust across writing tasks.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…In addition, the fluency effect in this research is consistent across writing genres. It echoes back to Conijn et al’s (2019) finding, that is, the features, particularly for within words, are robust across writing tasks.…”
Section: Discussionmentioning
confidence: 64%
“…As shown in Table 7 , the correlations related to the lower-level cognitive process component could tentatively be interpreted as the fluency effect , and modeling the WithinWord linguistic context data might reflect a measure of dysfluency with orthography. Orthography is the least demanding of the measured cognitive processes ( Deane et al, 2008 ; Deane et al, 2011 ; Conijn et al, 2019 ). If an 8 th grade student has too many pauses at the location of typing a word ( WithinWord pause data), it is more likely that he/she has difficulty spelling rather than that he/she is instead engaging with a higher-level cognitive process (e.g., word choice or intention reflection).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the majority of high-stakes language tests becoming computerized, and given the limitations imposed by verbal protocols and questionnaires, an increasing number of L2 process studies started to rely on new techniques such as keystroke logging programs to examine writing process (Almond et al, 2012;Barkaoui, 2016Barkaoui, , 2019Chukharev-Hudilainen, 2019;Conijn et al, 2019;Leijten & Van Waes, 2013;Miller et al, 2008;Révész et al, 2017;Zhang et al, 2017). Unlike verbal protocols, keystroke logging enabled researchers to collect writing process data in a non-invasive and natural context.…”
Section: Investigating L2 Writing Process In Assessment Contextsmentioning
confidence: 99%
“…The different tasks might lead to different writing processes, and consequently also different keystroke data. Previous work already showed that keystroke data is sensitive to small differences in writing tasks, such as copy writing versus email writing (Conijn et al, 2019). In addition, differences in source usage, such as independent and integrated tasks, have been shown to have an effect on students' pausing and revision behavior (Michel et al, 2020).…”
Section: Relation Between Keystroke Data and Writing Qualitymentioning
confidence: 99%